In vitro antibacterial activity of ethanol extract of Artemisia annua and its bioactive fractions against fish pathogens. (5th December 2020) - Soares, Michelly Pereira; Pinheiro, Victor Rossi; Cardoso, Israel Luz; Oliveira, Adriana da Silva Santos de; Sartoratto, Adilson; Ishikawa, Márcia Mayumi; Jonsson, Claudio Martin; Duarte, Marta Cristina Teixeira; Rantin, Francisco Tadeu; Sampaio, Fernanda Garcia
Abstract: Bacterial pathogens cause significant economic losses in fish farms worldwide. The frequent use of antibiotics is a growing concern due to the adverse effects on human health and the environment. We evaluate the antibacterial activity of the Artemisia annua and its bioactive components against the Aeromonas hydrophila, Streptococcus agalactiae and Flavobacterium columnare, the main bacteria that affect fish culture. Bioactive components of the A. annua were obtained using an alcoholic extraction process, yielding 10.6% of dry material. The alcoholic extract of A. annua (ae‐Aa) bioactive compounds was fractionated, obtaining the fractions F1 + 2, F3, F4, F5 and F6. Artemisinin up to 10.0 mg.ml ‐1 was ineffective in controlling studied bacteria. Microorganisms tested were all sensitive to ae‐Aa (MIC and MBC 0.40 to 2.50 mg.ml ‐1 ). The ae‐Aa components F3, F4, F5 and F6 were also effective (MIC and MBC 0.015 to 2.00 mg.ml ‐1 ). F3 showed the most effective antibacterial activity (MIC 0.015 to 0.5 mg.ml ‐1 and MBC 0.015 to 2.0 mg.ml ‐1 ). The ae‐Aa and its bioactive components presented efficacy to inhibit growth and eliminate bacterial pathogens and can be an alternative to synthetic antibiotics for farmed fish.